2022
DOI: 10.1186/s40794-021-00160-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and potential quality indicators for evaluating pre-travel consultations in Japan hospitals: the Japan Pretravel consultation registry (J-PRECOR)

Abstract: Background Awareness of pre-travel consultations (PTCs) and prevention methods for overseas travel-related diseases, and the understanding of PTCs among Japanese travelers and medical professionals remains low in Japan. A multicenter registry was established to examine PTCs in Japan. This study assessed the PTC implementation rate and examined the indicators of PTCs that can be used as criteria for evaluating quality. Methods Clients who presented … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Overall, the studies identified showed considerable heterogeneity in the inclusion of SRH content in travel medicine consultations. Rates varied between 8.3 and 84.1%, 34 , 38 , 39 although rates of inclusion were scarcely reported as a percentage. When using a Likert scale, the inclusion of SRH topics in consultations, as reported by HCPs, ranged from 19.7% of respondents ‘always’ providing relevant information 37 to 76% ‘usually’ providing advice.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, the studies identified showed considerable heterogeneity in the inclusion of SRH content in travel medicine consultations. Rates varied between 8.3 and 84.1%, 34 , 38 , 39 although rates of inclusion were scarcely reported as a percentage. When using a Likert scale, the inclusion of SRH topics in consultations, as reported by HCPs, ranged from 19.7% of respondents ‘always’ providing relevant information 37 to 76% ‘usually’ providing advice.…”
Section: Resultsmentioning
confidence: 99%
“… 28 , 30–33 , 35 , 39 Four studies were conducted in North America, 27 , 28 , 35 , 38 four in Europe, 30 , 31 , 36 , 39 three in Australia, 29 , 32 , 33 one in the Middle East 37 and one in Asia. 34 One study had a global sample by studying members of the International Society of Travel Medicine. 35 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations